Studies on the mechanisms of action of MR33317 - Joachim Neumann; C. Hesse; S. Yahiaoui; P. Dallemagne; C. Rochais; B. Hofmann; U. Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
MR33317 was synthesized as an acetylcholinesterase-inhibitor and an agonist at brain 5-HT 4 -receptors. MR33317 might be used to treat Morbus Alzheimer. This therapeutic action of MR33317 might be based on MR33317´s dual synergistic activity. We tested the hypothesis that MR33317 also stimulates 5-HT 4 -receptors in the heart. MR33317 (starting at 10 nM) increased force of contraction and beating rate in isolated atrial preparations from mice with cardiac confined overexpression of the human 5-HT 4 -serotonin receptor (5-HT 4 -TG) but was inactive in wild type mouse hearts (WT). Only in the presence of the phosphodiesterase III-inhibitor cilostamide, MR33317 raised force of contraction under isometric conditions in isolated paced (1 Hz) human right atrial preparations (HAP). This increase in force of contraction in human atrium by MR33317 was attenuated by 10 µM tropisetron or GR125487. These data suggest that MR33317 is an agonist at human 5-HT 4 -serotonin receptors in the human atrium. Clinically, one would predict that MR33317 may lead to atrial fibrillation.